The prevalence of mental disorders among intimate partner violence exposed and non-exposed Rwandans: Findings from a national cross-sectional survey. (April 2022) - Bahati, Claire; Rukundo, Gilbert; Nyirahabimana, Naome; Izabayo, Josias; Niyonsenga, Japhet; Sezibera, Vincent
Highlights: The rate of any mental disorder was significantly higher in female than male exposed to IPV. The rate of any mental disorder tripled in group exposed to IPV than the non-exposed. The Lifetime prevalence of IPV exposure was high in those who were divorced and widowed. Abstract: Despite mounting evidence indicating an increased risk of long-term mental disorders in Rwanda's general population, little is still known about the national prevalence of mental disorders among victims of intimate partner violence (IPV) in a post-conflict setting. The aim of this study was to compare the prevalence of mental disorders among IPV exposed and non-exposed individuals in Rwanda. This was a cross-sectional study based on secondary data from the 2018 Rwanda Mental Health Survey. The sample consisted 20, 381 participants selected nationwide, from 7, 124 households (age range: 14–65 years), of which 3, 759 Rwandans were exposed to IPV (18.4%) and 16, 622 were non-exposed to IPV (81.6%). Participants were screened for IPV exposure and common mental disorders, and data was analyzed using the SPSS version 25 software. The results showed that the rate of any mental disorder was substantially higher in the group exposed to IPV than the non-exposed, at 32.4% and 11.7% respectively. These results highlight that among Rwandans diagnosed with severe mental disorders, participants with a history of IPV exposure present with increased odds of mental disorders prevalence and severity. Therefore, people seeking mental health care should also be screened for their IPV exposure and offered appropriate interventions.